Demographic Shocks and Women's Labor Market Participation: Evidence from the 1918 Influenza Pandemic in India. (September 2022) - Fenske, James; Gupta, Bishnupriya; Yuan, Song
Abstract : How did the 1918 influenza pandemic affect female labor force participation in India over the short run and the medium run? We use an event-study approach at the district level and four waves of decadal census data in order to answer this question. We find that districts most adversely affected by influenza mortality saw a temporary increase in female labor force participation in 1921, an increase that was concentrated in the service sector. We find suggestive evidence that distress labor supply by widows and rising wages help account for this result.